Toxic Relationship: Its Effect on Mental Health in Adolescent Girls - Tampubolon, Viktoria Margaretha; Siahaan, Ervina M. R.; Pasaribu, Ronald P. (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
A toxic relationship is a relationship that makes the partner feel underestimated, this will of course affect the mental health of a person. The purpose of this study is to determine the influence of toxic relationships on mental health in adolescent girls in Medan City. This study uses a quantitative method, and the research subjects are 118 adolescent girls aged 18-21 years who already have a partner and live in the city of Medan. The results of the study showed that there was an influence of r = 0.301 with p = 0.001